Seed and Cone Production Patterns from Seventy-Nine Provenances of Pinus halepensis Mill. Across Tunisia Forests - Ayari, bdelaziz; Salah, Garchi; Daniel, Moya (Global Journal Of Botanical Science, 2014)
Pinus halepensis Mill. is an important tree species in the Mediterranean Basin. In Tunisia, there is an increasing interest in its seed production due to their impact on the socio-economical life of the Tunisian population, forest regeneration (seedling production) and biodiversity maintenance. Adaptative strategies were developed to fire recurrence by early cone production and seed storage in the serotinuous cones. Tunisia's native forests were investigated to examine the impact of four bioclimatic zones on Aleppo pine cone and seed production. Stand characteristics and average tree size measurements were studied with simple and multiple regression analyses for explaining their influences in seed and cone production and characteristics. Results showed a positive relationship between the accumulated rainfall and the geographical variables to the number of cones and its seeds content. Density had a strong adverse effect on the average tree's cone crop and seed yield. The cone production and the total seed mass were positively correlated with tree dimensions, but diameter at breast height and crown height were the most explanatory variables. Several environmental factors substantially increased the production of cones and seeds. The results could help foresters to decide better locations of cone and seed production according to density in Aleppo pine forests.